PENGARUH LATIHAN LOMPAT TALI DENGAN PERLAHAN TERHADAP TAHAN PADA TIM TENIS MEJA PUTRI SMA NEGERI OLAHRAGA PEKANBARU - Khairul Irwan; Ramadi Ramadi; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study was to determine how much influence the jump rope slowly had on endurance on the women's table tennis team at SMA Negeri Negeri Sports. This research has been carried out in the Yossudarso street no 103, which coincided with a table tennis cast at the State Sports High School. This research will be carried out in December 2019 until June 2020 by implementing 16 meetings. The population which is also a sample in this study is the Table Tennis Athletes of SMA Negeri Sports Sports with 6 people. Based on the results of research and data processing can be concluded as follows: there is a significant effect of slow jump rope training (X) with an increase in endurance (Y) in female table tennis athletes in Pekanbaru Sports High School. These results are indicated by the following research data: the amount of pretest data is 185.8 with an average value of 30.96 and the amount of post test data is 200.1 with an average value of 33.48. Then the analisis t ’test analysis yields a t-test of 3.53 and a t-table of 2.015. Means tcount (3,53)> ttable (2,015). It can be concluded that there is an effect of slowly jump rope training on the ability of female table tennis athletes in Pekanbaru State Sports High School.Key Words: Jump Rope Training, Slowly, Endurance Tennis Team